1998
DOI: 10.1523/jneurosci.18-21-09038.1998
|View full text |Cite
|
Sign up to set email alerts
|

Partial Inactivation of the Primary Motor Cortex Hand Area: Effects on Individuated Finger Movements

Abstract: After large lesions of the primary motor cortex (M1), voluntary movements of affected body parts are weak and slow. In addition, the relative independence of moving one body part without others is lost; attempts at individuated movements of a given body part are accompanied by excessive, unintended motion of contiguous body parts. The effects of partial inactivation of the M1 hand area are comparatively unknown, however. If the M1 hand area contains the somatotopically ordered finger representations implied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
91
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(104 citation statements)
references
References 57 publications
12
91
0
1
Order By: Relevance
“…Because in most primate species, M1c is buried in the anterior bank of the central sulcus, selective injury or inactivation has rarely been attempted. However, observations of M1 stroke patients (Kim 2001;Schieber 1999) and M1 inactivation in monkeys (Brochier et al 1999;Fogassi et al 2001;Kubota 1996;Schieber and Poliakov 1998) have demonstrated that caudal inactivation results in selective deficits in individuation of finger movements and relative preservation of reaching.…”
Section: Discussionmentioning
confidence: 99%
“…Because in most primate species, M1c is buried in the anterior bank of the central sulcus, selective injury or inactivation has rarely been attempted. However, observations of M1 stroke patients (Kim 2001;Schieber 1999) and M1 inactivation in monkeys (Brochier et al 1999;Fogassi et al 2001;Kubota 1996;Schieber and Poliakov 1998) have demonstrated that caudal inactivation results in selective deficits in individuation of finger movements and relative preservation of reaching.…”
Section: Discussionmentioning
confidence: 99%
“…Rizzolatti and Luppino, 2001;Shelton and Reding, 2001;Olivier et al, 2007;Brown and Teskey, 2014). In monkeys, alterations of hand movements have been reported after unilateral transient inactivation or permanent lesion of M1 followed by the occurrence of compensatory strategies, affecting motor parameters such as force (Brochier et al, 1999), trajectory (Cirstea and Levin, 2000), precision grip (Brochier et al, 1999;Darling et al, 2009Darling et al, , 2011bDarling et al, , 2013Darling et al, , 2014Kermadi et al, 1997;Liu and Rouiller, 1999;Kaeser et al, 2010;Hoogewoud et al, 2013;Morecraft et al, 2015Morecraft et al, , 2016Wyss et al, 2013;Murata et al, 2015), flexion-extension (Schieber and Poliakov, 1998) and wrist movement (Hoffman and Strick, 1995). Depending on the size and location of the injury, spontaneous recovery occurs to a variable extent, though it is generally incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Because lesions of the corticospinal (CS) tract often impair irremediably dexterous finger movements (Forssberg et al, 1999;Duque et al, 2003;Hermsdorfer et al, 2003), the contribution of the CS system [and that of its main cortical area of origin, the primary motor cortex (M1)] to such movements has been extensively studied (Muir and Lemon, 1983;Schieber and Poliakov, 1998;Brochier et al, 1999).…”
Section: Introductionmentioning
confidence: 99%